Hyponatraemia: the importance of obtaining a detailed history and corroborating point-of-care analysis with laboratory testing. Issue 12 (9th December 2019) - Lim, Su Yin; Bodagh, Neil; Scott, Gregory; Hill, Neil E
Abstract : We describe a 67-year-old man admitted from a mental health unit with an incidental finding of hyponatraemia on routine blood tests. Laboratory investigations were in keeping with syndrome of inappropriate antidiuretic hormone secretion (SIADH). He had been recently commenced on mirtazapine. During his inpatient stay, he became increasingly confused. Review of a previous admission with hyponatraemia raised the possibility of voltage-gated potassium channel antibody-associated limbic encephalitis, although subsequent investigations deemed this unlikely as a cause of hyponatraemia. Although his sodium levels improved with fluid restriction, serial point-of-care testing proved misleading in monitoring the efficacy of treatment as inconsistencies were seen in comparison with laboratory testing. The cause of hyponatraemia may have been medication-induced SIADH and/or polydipsia. This case highlights the importance of collating detailed histories and laboratory blood testing to guide management in cases of hyponatraemia of unknown aetiology.